Between Lipany and White Mountain : essays in late medieval and early modern Bohemian history in modern Czech scholarship - Palmitessa, James R. (Studies in Central European histories, 2014)
This book presents twelve essays by Czech historians on the history of the Czech lands from the middle of the fifteenth to the middle of the seventeenth century, previously published in Czech, which appear here for the first time in English.